(جودة وإتقان إلتعليم في إلمنهج إلإسلامي (المفهوم -إلمبادئ- المحاور -الشروط (Journal of Faculty of Education, 2021)
The study aims at identifying extent Islam is interested in mastering education and to revealing the existence of terms that mean quality and mastery of education . Also , to determine the most important conditions required in the educational process to ensure the quality , mastery and excellence of education .Since the legal texts are certainty issues or recognized principles , the researcher used the deductive method to capture the educational principles and rules by tracking Quran Verses and Prophetic Sayings and the sayings of the good Salaf and the jurisprudence of the Muslim education scholars related to the quality of education as evidence and as influencing factors on the existence of quality.The research has reached a number of outcomes , the most important of which are: The Islamic school of thought has included a number of terms that benefit the mastery and the quality ( such as fidelity , benevolence , reform and mastery ) and the Muslim individual had to practice these terms or meanings practically in his daily life because they are all acts of worship to his Creator ( God , the Great and Almighty) , whenever intention and good work are fixed. The results also showed that mastering and quality of education in the Islamic school of thought are based on a genuine basis of principles , including : Fullawareness of the purposes of Islamic Sharia , the status of knowledge and acting scholars , the virtue of teaching and learning in Islam. The results have also indicated that the Muslim State is responsible and the sole guarantor of mastering education through its duty to Sanctify knowledge , scholars and knowledge seekers and by providing the optimum environment necessary for mastering education . The research also stressed the importance of having specific conditions for the educational process (teacher , learner , curriculum , school environment and educational administration ) to ensure the mastery and quality of education and the protection of society from all forms of professional fraud.In the light of the previous findings the research came out with a number of recommendations for mastering education , including : The school curricula should highlight the values of knowledge , scholars and knowledge seekers , and introduce the concepts of mastering education ( such as fidelity , mastery and benevolence) in teachers training programs and the profession ethics .
Keywords: المنهج الإسلامي; علماء التربية